As contribuições das linguagens de marcação para a gestão da informação arquivística digital - Gama, Fernando Alves da [UNESP] (2011)
This Project develops a dialogue among the Information Science, Archival Science and Information of Technology to show the benefits that markup language can bring to the management of archival documents trough the representation of classification tools and the preservation of digital records. The main objective of Archival science is the treatment of business information, through the treatment given to the records, which are produced by an individual or institution in the performance of their duties. Such documents are submitted to two user groups, whose behavior is linked to the informational use of the primary value of an administrative nature, in the current phase and intermediate and then the secondary value of its information, at the stage of permanent custody. This Project seeks to bring in a design set of metadata required for the representation of content, context and structure documentary directed to the needs of users. They will be presented in sequence, markup languages and the modeling of the semantic web as structures for the representation of metadata. After that the study will move into the users’ information behavior on the current phase and its interaction with the form of organic information. It displays the document management program and all the methodological process on its consolidation, followed by an explanation surrounding the production of documentary classification tools that promote vocabulary control in the management of documents, namely, Classification Plan and Australian Function’s Thesaurus. These tools are complementary and provide reliability and accuracy in information retrieval organic in all stages of document management. They also allow the representation of the context of document production to be analyzed by users of the phase of the standing guard. Then we will present the XML markup languages and modeling in RDF, RDFS and... (Complete abstract click electronic access below)